POLA KONSUMSI DALAM ISLAM DAN KONSEP ECO-SUFISME MUHAMMAD ZUHRI - Suwito Suwito (IBDA` : Jurnal Kajian Islam dan Budaya, 2011)
This article explores a new view of the relationship between theconsumption patterns and spiritual transformation, which is discussed ina Sufi perspective. Hunger tradition as Sufi’s consumption pattern is seenby Muhammad Zuhri as a medium for self-recognition. If someone hasbeen able to get to know himself, then it will gradually know the qualityof himself. Humans, is individually a weak creature, can not live withoutthe help of another man and the universe. In this context, the cosmos andthe self is "Theophany" of God. Humans are as caliph who serve the Lordand at the same time taking care of the universe. Fasting in religionsteach this consciousness. Fasting as one of the Sufi tradition have multifunction, namely as a means for someone to be close to God, man, andthe universe.